Airline Collocation: Frequency Based Analysis with COCA as a Corpus - Natalia, Bonifasia Ekta Fima (JET ADI BUANA, 2023)
Collocations are words that co-occur together in any text and have definite association. The use of collocations is part of linguistic awareness which defines how language is used naturally. This study aims to analyze the collocations used in airlines by using Corpus of Contemporary American English (COCA). The data were analyzed both quantitatively and qualitatively. Quantitatively, the data were calculated regarding the frequency, topics and cluster. Qualitatively, the data were verbally analyzed, described, and discussed. The big data is taken from 1990-2019. The frequent words in area of airlines management found in COCA are used as keywords to find concordance of other words or phrases. The results of the study shows that from the three words taken from the script of flight announcement in airport ‘flight’, ‘passenger’, and ‘boarding’ it was found that the frequency risen is 73,870. The topics related to the three words of airlines found is 22,798. The clusters found from the three words by COCA is 34,006 which ‘flight’ word has the largest clusters (18,730). From the COCA analysis, the new words or idioms related to airlines can be used as teaching material in vocabulary for aviation or airlines students.